2020
DOI: 10.1002/bdd.2222
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a de‐immunization strategy for monoclonal antibodies using cynomolgus macaque as a surrogate for human

Abstract: The immunogenicity of biotherapeutics presents a major challenge during the clinical development of new protein drugs including monoclonal antibodies. To address this, multiple humanization and de-immunization techniques that employ in silico algorithms and in vitro test systems have been proposed and implemented. However, the success of these approaches has been variable and to date, the ability of these techniques to predict immunogenicity has not been systematically tested in humans or other primates. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Monoclonal antibodies (mAbs) excellent drug candidates due to their high antigen specificity, also have favorable PK properties and engineer-friendly modular structure compared to small molecules (Sullivan et al, 2020). Beginning with the approval of the first monoclonal antibody rituximab for hematological tumor therapy in 1997, this targeted therapy branch has been shown to significantly enhance tumor therapy, bringing high specificity and minimal off-site toxicity (Kovalova et al, 2020). Meanwhile, previous investigations have confirmed that IL-35 plays an important role in liver diseases.…”
Section: Future Expectationmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) excellent drug candidates due to their high antigen specificity, also have favorable PK properties and engineer-friendly modular structure compared to small molecules (Sullivan et al, 2020). Beginning with the approval of the first monoclonal antibody rituximab for hematological tumor therapy in 1997, this targeted therapy branch has been shown to significantly enhance tumor therapy, bringing high specificity and minimal off-site toxicity (Kovalova et al, 2020). Meanwhile, previous investigations have confirmed that IL-35 plays an important role in liver diseases.…”
Section: Future Expectationmentioning
confidence: 99%